The ordinances of governmentba translation of Al-Aḥkām al-Sulṭāniyya wʼ al-Wilāyāt al-Dīniyya /cAl Mawardī ; translated by Wafaa H. Wahba - Māwardī, ʻAlī ibn Muḥammad 974?-1058 (Great books of Islamic civilisation, 1996)
Abu al-Hasan al-Mawardi was a 10th-century jurist who wrote on many subjects, including Qur'anic interpretations, religion, government, public and constitutional law, language and ethics. This is the first English translation of one of his key texts